THE RELATIONSHIP OF STIGMA WITH FAMILY DECISION MAKING IN TREATMENT OF MENTALLY DISORDERED PATIENTS - Maresa Viana; Niken Yuniar Sari; Miranti Dea Dora (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
The inappropriate comprehension of family about treating mental disorders patients cause a bad mindset that can be seen by the family's assumption, this disease is an incurable disease so that the family tends to allow the patients as long as they don’t interfere.The aim of study determined the correlation of stigma with the family decisions making in treating mental disorders patients in the Mental Hospital of Lampung Regional 2022.The quantitative type study, analytical design with cross sectional method. The population were all of mental disorders patients in the Mental Hospital of Lampung Regional in July till April 2022, as many as 667 patients and the sample number of 123 respondents. In this study, the sampling technique used purposive sampling. Based on the statistical tests results, obtained p-values ​​was 0.001 (stigma) p-value < value (0.05) that there were a correlationof stigma status with the family decisions making in treating mental disorders patients in the Mental Hospital of Lampung Regional 2022.This study is expected to enable the families to make decisions in providing treatment.